1987
DOI: 10.1073/pnas.84.10.3185
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA topoisomerase I in the transcription of supercoiled rRNA gene.

Abstract: The fraction DE-B obtained by fractionating an extract from rat mammary adenocarcinoma cells on a DEAE-Sephadex column was used for transcribing linear and supercoiled rRNA gene (rDNA). This fraction, which is known to contain RNA polymerase I and essential transcription factors, also contains DNA topoisomerase I activity. Inhibition of this topoisomerase activity by the selective inhibitor camptothecin markedly diminished transcription of supercoiled rDNA, and at a concentration of 150 ,uM, camptothecin almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…Moreover, p14 ARF and Topo I are both recovered in the chromatin fraction containing the rRNA promoter (Ayrault et al, 2004), in accordance with the requisite role of Topo I in rRNA transcription through the relaxation of supercoiled rDNA (Garg et al, 1987). We examined the possible involvement of p14 ARF in cell cycle arrest through both its activation of Topo I catalytic activity and inhibition of rRNA transcription.…”
Section: H358wtmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, p14 ARF and Topo I are both recovered in the chromatin fraction containing the rRNA promoter (Ayrault et al, 2004), in accordance with the requisite role of Topo I in rRNA transcription through the relaxation of supercoiled rDNA (Garg et al, 1987). We examined the possible involvement of p14 ARF in cell cycle arrest through both its activation of Topo I catalytic activity and inhibition of rRNA transcription.…”
Section: H358wtmentioning
confidence: 80%
“…We had previously described the existence of an interaction between p14 ARF and the topological enzyme Topoisomerase I (Topo I), essential in the transcription of supercoiled rRNA genes (Garg et al, 1987;Karayan et al, 2001;Ayrault et al, 2003). More recently, we have demonstrated by ChIP experiments that p14 ARF protein was able to specifically interact with the human rRNA promoter in the presence of Topo I (Ayrault et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have indicated that this enzyme which interconverts topological isomers of DNA by breaking and resealing one DNA strand, is required for proper transcription ofrRNA genes (e.g. Garg et al, 1987;Egyhazi and Durban, 1987;Rose et al, 1988;Zhang et al, 1988;Kim and Wang, 1989). Topoisomerase I has been shown to be associated with RNA polymerase I and is located within the transcribed region of the rRNA genes but absent from the spacer region (Zhang et al, 1988).…”
Section: B Immunolocalization Of Dna Topoisomerase Imentioning
confidence: 99%
“…Although their biological function is not completely defined , this class of topoisomerase has been implicated in transcriptional (Akrigg and Cook 1980;Dynan and Burgess 1981;Sternglanz et al 1981;Weisbrod 1982;Fleischmann et al 1984 ;Gilmour et al 1986;Shastry 1986) as well as in recombinational and replicational (Kikuchi and Nash 1979 ;Sternglanz et al 1981 ; also see Gellert 1981 ;Bullock et al 1985 ;Zeng et al 1985) events. J n higher eukaryotes topoisomerase I is enriched in the nucleolus (Fleischmann et al 1984;Muller et al 1985) and may play a role in transcription of supercoiled rDNA in vitro (Garg et al 1987). Studies in Tetrahymena indicate that the ribosomal DNA-associated enzyme…”
Section: Introductionmentioning
confidence: 99%